2022
DOI: 10.1136/jim-2021-002071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between circulating serum omentin-1 levels and nascent metabolic syndrome in patients with hypertension

Abstract: The prevalence of metabolic syndrome (MetS) is more common in patients with hypertension and is associated with an increased risk of target organ damage and/or cardiovascular disease (CVD). Omentin-1 is a beneficial adipokine considered to play a role in MetS and MetS-related states such as obesity, diabetes, and coronary artery disease. The aim of this study was to determine the relationship between circulating omentin-1 levels and MetS uncomplicated by diabetes or CVD (nascent MetS) in patients with hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…In human studies, serum omentin-1 concentrations were lower in obese patients and inversely correlated with the markers of obesity [ 78 ], metabolic syndrome [ 79 ] and diabetic complications [ 80 ]. Low omentin-1 level has been suggested to be a reliable marker to predict the development of MetS in patients with hypertension [ 81 ]. Indeed, omentin-1 was lower in both pre- and postpubertal obese children with metabolic syndrome compared to obese children without metabolic syndrome.…”
Section: Role Of Novel Adipokines In Non-diabetic Obesitymentioning
confidence: 99%
“…In human studies, serum omentin-1 concentrations were lower in obese patients and inversely correlated with the markers of obesity [ 78 ], metabolic syndrome [ 79 ] and diabetic complications [ 80 ]. Low omentin-1 level has been suggested to be a reliable marker to predict the development of MetS in patients with hypertension [ 81 ]. Indeed, omentin-1 was lower in both pre- and postpubertal obese children with metabolic syndrome compared to obese children without metabolic syndrome.…”
Section: Role Of Novel Adipokines In Non-diabetic Obesitymentioning
confidence: 99%
“…Omentin-1 levels have been demonstrated to be lowered in dysmetabolic conditions, including diabetes mellitus [5,11,44], obesity [11], and impaired glucose tolerance [45]. Indeed, omentin-1 is downregulated by glucose/insulin levels [4].…”
Section: Insulin Sensitivitymentioning
confidence: 99%
“…Omentin-1's positive effects on vascular function, including vasodilation, anti-inflammatory actions, and potential anti-atherosclerotic effects, suggest potential applications in cardiovascular diseases [72,73]. Therapies aimed at increasing omentin-1 levels or enhancing its activity could be explored for conditions such as atherosclerosis, hypertension, and other cardiovascular disorders [45,55,74].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…In addition to mediating insulin resistance, previous studies have shown that omentin-1 played a crucial role in anti-inflammation, anti-oxidation, and regulation of apoptosis ( 12 14 ). It has been demonstrated that decreased circulating omentin levels are associated with MetS as well as MetS comorbidity with obesity, carotid atherosclerosis, and hypertension ( 15 18 ). Another meta-analysis found that the omentin levels in patients with type 2 diabetes mellitus (T2DM) were significantly lower than those in controls, and lower omentin levels increased the risk of complications in patients with diabetes ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%